Systematic quality work in preschools: Principals’ prioritized improvement measures for increased quality - Mikael Segolsson; Lene Foss (Nordisk Barnehageforskning)
Systematic quality work (SQW) has become a large part of principals’ work in preschools. This study investigates principals’ priorities in SQW in preschools and identifies measures they implement to reach quality and improvement goals. The collected research data consists of 63 action research reports written by the principals as part of an education training program. The researchers investigated these reports through document analysis and thematic content analysis, which generated five themes. The results demonstrate that the majority of the improvement measures prioritized by the principals are implemented according to a top-down principle and that the improvements are primarily about creating the conditions for SQW at a structural level. Furthermore, the results show that the principals develop templates for joint documentation with the aim of supporting the preschool teachers in their work, but also for everyone to document in the same manner. The most interesting result is that few of the principals’ prioritized improvement measures pertained to the national goals in terms of children’s development and learning, suggesting a discrepancy between expected and officially pronounced national goals for improvement measures in preschools and principals’ prioritized actions for enhancements.